Pengaruh Kualitas Pelayanan, Reputasi Perusahaan, Dan Kepuasaan Nasabah Dalam Menciptakan Loyalitas Nasabah Pada Penggunaan Mobile Banking Di Pt Bank Xyz - Octario Edo Setyawan dan Anas Lutfi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to analyze the quality of service, reputation and loyalty of customers to mobile banking user loyalty at Bank XYZ. In addition, it can provide valuable input for customers in maintaining and improving service quality and customer satisfaction. This research uses qualitative methods and is included in survey research. Data to be used is the primary data obtained through the distribution of questionnaires. This, in this study is a Bank XYZ loan. The number of surveys will be conducted on 122 people who have used mobile banking at Bank XYZ. According to Aritonang (2007), the minimum number of respondents is 5 times from the question point, that is 5 x 22: 110 obtained from the number of respondents is 122. The research period is cross sectional where the data is done at one time. Time is done in the period April - May 2018. Data analysis is done using statistical analysis with multiple linear regression analysis with the help of SPSS program version 24.00. The results showed that customer satisfaction and satisfaction proved to have positive and positive impact on customer loyalty at PT Bank XYZ. Quality of service and customer satisfaction is very influential as much as 61.6% of customer loyalty. The company's reputation proved to have no effect on customer loyalty in PT Bank XYZ because it has a sig value> 0.05.